The Relational Dimension of Identity—Theoretical and Empirical Exploration - Lopes, H.; Calapez, T. (Review of Social Economy, 2012)
Identity has been recently introduced as a "legitimate" subject matter in economics. Whereas the social nature of identity is consensually acknowledged, its relational and moral dimensions are overlooked. We begin by clarifying the role of interpersonal relations in identity formation. Following Honneth (1995) we argue that the development of a positive identity, defined as a person's relation-to-self, depends on the processes of mutual recognition in which a person takes part throughout her/his life. We then frame Honneth's recognition processes in terms of the access to relational and moral goods. An empirical study is presented that illustrates the association between relational and moral goods and "relation-to-self." Based on European Social Survey (ESS) data, we show that high levels of relational goods (e.g. experiencing intense and positive social relations) and moral goods (e.g. perceiving to be treated with justice and respect) are associated with a positive relation-to-self.